2019
DOI: 10.1289/ehp3523
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Exposure to Select Phthalates and Phenols and Associations with Fetal and Placental Weight among Male Births in the EDEN Cohort (France)

Abstract: Background: The placenta performs crucial physiological functions to ensure normal fetal development. Few epidemiological studies investigated placental weight sensitivity to phthalates and phenols. Objective: Our goal was to explore whether maternal exposure to select phthalates and phenols is associated with changes in placental weight at birth and in placental–to–birth weight ratio (PFR). Methods: Placental weight and birth weight were ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
1
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(58 citation statements)
references
References 48 publications
1
48
1
8
Order By: Relevance
“…From 15 selected studies, 12 studies were cohort and 3 studies were cross-sectional studies. The number of studies that reported the association of TCS exposure with birth weight, birth length, birth head, and gestational age was 13,[ 4 7 10 11 12 18 19 20 21 22 23 24 25 ] 9,[ 4 6 7 11 12 18 22 23 26 ] 8,[ 4 6 7 12 18 19 22 26 ] and 6,[ 4 6 11 12 22 25 ] respectively. All studies had evaluated the prenatal exposure to TCS and growth in both male and female neonates, except 2 studies that investigated it in male infants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From 15 selected studies, 12 studies were cohort and 3 studies were cross-sectional studies. The number of studies that reported the association of TCS exposure with birth weight, birth length, birth head, and gestational age was 13,[ 4 7 10 11 12 18 19 20 21 22 23 24 25 ] 9,[ 4 6 7 11 12 18 22 23 26 ] 8,[ 4 6 7 12 18 19 22 26 ] and 6,[ 4 6 11 12 22 25 ] respectively. All studies had evaluated the prenatal exposure to TCS and growth in both male and female neonates, except 2 studies that investigated it in male infants.…”
Section: Resultsmentioning
confidence: 99%
“…All studies had evaluated the prenatal exposure to TCS and growth in both male and female neonates, except 2 studies that investigated it in male infants. [ 18 21 ]…”
Section: Resultsmentioning
confidence: 99%
“…[63][64][65] It is accepted that early disruption to peri-implantation processes such as alterations in embryo spacing or development, decidualization, and placentation may perpetuate throughout pregnancy, manifesting later as preterm birth, among other adverse outcomes. 66 Based on previous results from the EARTH Study team and those of others, including fertile populations, we hypothesize that an early action of DEHP metabolites at the ovary may interfere with normal fertility and implantation processes, 67,68 predisposing to a syndrome of complications throughout gestation that may be associated with altered placental function, 69,70 embryo and fetal growth restriction, 71 preeclampsia, 72 pregnancy loss, 73 and ultimately preterm birth. Of relevance for preventive care, this syndrome could have its roots in the preconception or periconception period.…”
Section: Discussionmentioning
confidence: 98%
“…Phthalates can cross the placental barrier as a result of continuous exposure during pregnancy, with profoundly negative consequences for the future health of infants, by increasing the risk of developing defects such as low birth weight, cardiovascular diseases, cryptorchidism, and cancer later in life [111,112]. The metabolites of DEHP have been detected by mass spectrometry in amniotic fluid.…”
Section: Phthalatesmentioning
confidence: 99%